PRINSIP-PRINSIP PENGGUNAAN BAHASA SEBAGAI ALAT KOMUNIKASI INTERAKTIF DAN MENJALIN HUBUNGAN BAIK - Siti Habibah; Welsa Aini; Silvina Noviyanti (STKIP Subang, 2024)
Humans need communication to help survive, one of which is by using language as a communication tool. Language is the most effective communication tool in conveying messages, thoughts, feelings, goals to other people and makes it possible to create cooperation between people. So that the role of language becomes very dominant in various daily human activities. The aim of this research is to describe things related to language as a means of communication and communication in everyday life. The method used in this research is the literature review method, data is collected from relevant library data. The results of this research and discussion are to explain language as a communication tool which discusses the function of language as a human communication tool which includes five basic functions, namely the expression function, information function, exploration function, persuasion function and entertainment function. And explains communication in everyday life, which discusses why we communicate and the language used when communicating in everyday life. As social creatures, of course humans in their lives need communication to be able to establish relationships with other humans. Language is the most effective tool or medium for conveying thoughts, with language humans can interact and talk about anything.